The complete chloroplast genome of Euphorbia prostrata (Euphorbiaceae) - Ami Oh; Eun Su Kang; Dong-Chan Son; Soo-Rang Lee (Mitochondrial DNA. Part B. Resources, 2024)
AbstractEuphorbia prostrata Aiton 1789, an annual herb, is native to tropical and subtropical Americas and was introduced into many parts of the Old-World including Korea. We determined the genomic characteristics of the complete chloroplast genome of E. prostrata with a de novo assembly strategy. The complete chloroplast genome was 162,858 bp long, and harbored 86 protein coding, 37 tRNA and 8 rRNA. The genome showed the typical quadripartite structure consisting of a large single copy (LSC) (90,580 bp), a small single copy (SSC) (18,570 bp) and a pair of inverted repeats (IRs) (26,854 bp). The phylogenetic tree inferred from chloroplast genomes of 25 taxa, which belong to Euphorbiaceae indicated that the Euphorbia is a monophyletic group and E. prostrata is closely related with E. humifusa, E. thymifolia and E. hirta, forming a well-supported clade. Our findings can be valuable for understanding the phylogenetic relationships and the evolution in Euphorbiaceae and will provide basic information for future studies on E. prostrata from genomic perspective.